Project Construction for Undergraduate Non-Engineering Seniors - Beard, F. Richard; Miller, Bruce E. (Journal of Agricultural Systems, Technology, and Management, 2007)
A senior level design course for non-engineering undergraduates provides the opportunity for students to develop and exercise creative and imaginative talents in the design of agricultural projects. The course emphasizes an agricultural systems approach and involves group and individual design activities based on standard design principles. The course resembles employment in a professional occupation where assignments are given and “employees” are expected to successfully complete such activities in a timely manner, with minimum supervision. Common instructional problems are related to students with little or no experience in design principles, limited math skills, and the increasing tendency for agricultural students to lack traditional agricultural mechanics skills. Smaller group projects are completed at the beginning of the course and each student must complete an individual final design project. Biweekly PowerPoint presentations depicting progress toward completion are required throughout the course and a final poster presentation accompanies the prototype design project displayed at the end of the course.